2013
DOI: 10.1007/s13238-013-3088-8
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 accelerates xenogeneic graft-versus-host disease correlated with increased B-cell proliferation

Abstract: Graft-versus-host disease (GVHD) is a prevalent and potential complication of hematopoietic stem cell trans-plantation. An animal model, xenogeneic GVHD (X-GVHD), that mimics accurately the clinical presentation of GVHD would provide a tool for investigating the mechanism involved in disease pathogenesis. Murine models indicated that inhibiting IL-21 signaling was a good therapy to reduce GVHD by impairing T cell functions. We sought to investigate the effect of exogenous human IL-21 on the process of X-GVHD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…More specifically, IL-21 promotes the expansion of ST-HSCs and MPPs within the BM-resident LSK population, which represents the source of building blocks required for rapid immune recovery [ 49 , 51 55 ]. Although not directly assessed in our studies, we presume that such increase in the pool of BM progenitors enhances thymic seeding [ 60 , 73 ]. In parallel, we demonstrated that IL-21 stimulates intrathymic T cell development directly by boosting the count of thymic progenitor cells while enhancing TEC recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, IL-21 promotes the expansion of ST-HSCs and MPPs within the BM-resident LSK population, which represents the source of building blocks required for rapid immune recovery [ 49 , 51 55 ]. Although not directly assessed in our studies, we presume that such increase in the pool of BM progenitors enhances thymic seeding [ 60 , 73 ]. In parallel, we demonstrated that IL-21 stimulates intrathymic T cell development directly by boosting the count of thymic progenitor cells while enhancing TEC recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This is counterintuitive as GVT is usually associated with GVHD induction [ 65 ]. Furthermore, the IL-21/IL-21R signaling axis was previously reported to exacerbate GVHD in a CD4-dependent manner involving B cell expansion and production of autoantibodies [ 73 , 90 , 91 ]. Our study puts at play two important factors, which may help depict the discrepancy between our observations and those reported by others.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies were performed in the isolated murine setting, IL-21 has not only been shown to be a key mediator of murine acute GVHD 39,40 but also of xenogeneic GVHD induced by human lymphocytes. 21,41 Here, we show that a blockade of the common g chain, which is required for the function of the receptors for IL-2, IL-4, IL-7, IL-9, IL-15, and IL-21, reduced acute GVHD significantly in mice with respect to survival, inflammatory cytokine levels, and histopathological GVHD severity. In line with this potent reduction of acute GVHD in the mouse model, in patients, the plasma levels of IL-7 and IL-15 measured 30 days after both myeloablative 35 and nonmyeloablative allo-HCT 42 were highly predictive biomarkers of acute GVHD.…”
Section: Discussionmentioning
confidence: 77%
“…The inhibition of IL-21 signaling was a good therapy to reduce GVHD by impairing T cell functions. Compared with the control group, IL-21 induced robust Ig secretion, which was accompanied by increased accumulation of CD19 + CD38 high plasma cells in spleen [63]. IL-22, which produced by Th22, Th1, and Th17 cells, plays a pathogenic role in the GVHD process.…”
Section: Cytokines Involved In Gvhdmentioning
confidence: 85%